mRNA semen-specific markers for body fluids and tissue identification in forensic ge-netics - Iva Gomes; Daniela Borges; Laura Cainé (RevSALUS)
The identification of body fluids using (m)RNA is crucial to provide details about the crime circumstances in forensic genetic investigations [1-3]. While DNA identification gives information on the identity of the donor of a biological stain, RNA analysis allows for the detection of expressed genes by different cell types [1]. The expression of specific mRNAs varies depending on the cell or tissue, therefore, with an mRNA-based assay it is possible to identify the type of biological fluid that makes up a tissue [2, 3]. Reports of high stability of RNA markers with tissue-specific expression patterns have also been described, allowing the identification of relevant human cell types in small amounts of samples, as well as, in degraded material [2, 3]. In the context of sexual violence, seminal fluid is one of the most relevant fluids. In a latter scenario where an ejaculation has occurred, the investigation depends mainly on the cytological detection/ visualization of sperm. However, the absence of sperm does not always indicate the absence of semen [1]. The main goal of the present study was to validate four recently and newly described mRNA markers for potential identification of semen in forensic settings [4]. For this, a multiplex system containing the mRNAs (ODF1, SMCP, TcP11 and TNP1) as well as two commonly used markers (PRM1 and SEMG1) was developed. The potential application of this multiplex in samples from forensic backgrounds was evaluated through testing of: i) sensitivity using RNA concentration inputs ranging from 5 ng/ml to 0.02 ng/ml; ii) specificity by cross reactivity assessment on vaginal secretions, saliva and menstrual blood samples; and iii) degradation assessment on semen samples up to 18 months old since collection. The proposed markers, ODF1, SMCP, TcP11 and TNP1, can serve as a possible molecular alternative for semen identification to the traditional techniques since high sensitivity high specificity as well as detection in aged samples was confirmed in this study.